Sosialisasi dan Edukasi Penilaian Mandiri terhadap Risiko Penularan COVID-19 melalui InaRISK Personal - Sufiyanto Sufiyanto; Sari Yuniarti; Djoko Andrijono (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2020)
The implementation of the COVID-19 protocol was carried out as part of an effort to revive the economy that slumped due to the COVID-19 pandemic. Public awareness in implementing COVID-19 protocols is important in the New Normal life rules. This service activity helps the community to carry out an independent assessment of the risk of spreading and transmitting the COVID-19 virus. Also, it provides education and raises awareness to the public regarding health protocols. This method uses the InaRISK Personal application developed by the National Disaster Management Agency or Badan Nasional Penanggulangan Bencana (BNPB). The community as respondents is helped to obtain an independent assessment by filling in the answers to the questionnaire into the InaRISK Personal application. The results showed that 57.2% had low-risk status, 40.3% medium risk, and 2.5% high-risk status. Some of the behaviors that have the potential to increase the risk of contracting the COVID-19 virus are 89% of respondents touching money and 86.3% traveling for the risk of contracting outside the home, 55.5% of respondents do not provide hand sanitizers at home for the risk of contracting at home, 46, 8% of respondents did not drink vitamins C and E and lack of sleep for risks related to immunity. The conclusion is that the public still needs to increase awareness in carrying out health protocols to reduce the risk of spreading and transmitting the COVID-19 virus.DOI: https://doi.org/10.26905/abdimas.v5i3.5004